Economic, health and physical impacts of covid-19 pandemic in sub-saharan african regions: A cross sectional survey - Mashige, K.P.; Osuagwu, U.L.; Ulagnathan, S.; Ekpenyong, B.N.; Abu, E.K.; Goson, P.C.; Langsi, R.; Nwaeze, O.; Timothy, C.G.; Charwe, D.D.; Oloruntoba, Richard; Miner, C.A.; et al. (DOVE MEDICAL PRESS LTD, 2021)
Purpose: The key preventive measures adopted to minimise the spread of the coronavirus disease (COVID-19) had significant health, economic and physical impacts mostly in developing countries. This study evaluated the health, economic and physical impacts of COVID-19 lockdown measures among sub-Saharan African (SSA) population and associated demographic variations. Methods: A total of 1970 respondents took part in this web-based cross-sectional survey during the mandatory lockdown period in most SSA. The dependent variables were health (COVID-19 infection, hospitalisation), socioeconomic (lost job, closed down business) and physical impacts (separated from family) of COVID-19. Univariate and bivariate logistic regression analyses were used to explore the factors associated with each of the dependent variables by the four sub-regions (Southern, Western, Central and East Africa). Results: The respondents were aged 34.1 ± 11.5 years (range: 18–75 years) and mostly men (1099, 55%). 25.9% (n = 511) reported an impact of COVID-19 pandemic with significant regional variations (p < 0.0005, higher proportion were East 36.2% and Southern Africans 30.3%) but no gender (p = 0.334) and age group variations (p > 0.05). Among Central African respondents, more men than women lost their businesses (45.7% versus 14.3%, p = 0.002) and contracted COVID-19 infections (40.0% versus 18.2%, p = 0.024) during the study period. Multivariable analysis revealed that respondents from East (adjusted odds ratio [AOR] 1.95, 95% confidence interval [CI]: 1.42–2.69), Southern (AOR 1.46, 95% CI: 1.09– 1.96) and Central Africa (AOR 1.47, 95% CI: 1.06–2.03) reported significantly higher impact of COVID-19. Those who reported family separation during the lockdown were more likely to be older participants (39–48 years, AOR 2.48, 95% CI: 1.11–5.57). Conclusion: One in four SSA respondents, mostly East and Southern Africans, were adversely affected by the COVID-19 pandemic during the lockdown. Interventions in high-risk populations are needed to reduce the health, socioeconomic and gender disparities in the impacts of COVID-19.